The Evolution of E-Commerce: Data-Driven Insights and Future Trends - Annapureddy, Govardhan Reddy (Eastasouth Institute, 2024)
The dynamic nature of change is evident from the fact that it is prompted by such factors as advancements in technology and shift in consumers’ behavior for E-commerce operations. The following paper will look at four developing industry trends that include artificial intelligence as well as artificial intelligence mobile commerce or social commerce as well as sustainability. The integration of artificial intelligence with the mobile commerce makes personalization and logistic improvements while providing a more tailored buying experience with the help of the deployment of the smartphones and AR technologies in Shopping. Social commerce enables the consumers to buy products through social media networks which in turn affect their buying decisions.